TRANSFORMASI GENDER DALAM KELUARGA MULTIKULTURAL - Damiri, Damiri (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2023)
This study examines the transformation of gender roles in multicultural families in the midst of globalization and migration. Using a literature study approach, this article analyzes how traditional gender roles are adapted and changed in different cultural contexts. The findings suggest that education, migration, and local cultural influences play an important role in driving gender role change. However, the process also faces various challenges, including internal conflicts and social pressure from the community. This article identifies effective conflict resolution strategies, such as open communication, compromise, and community support, that can help multicultural families achieve equality and harmony. In conclusion, gender transformation in multicultural families has a significant impact on emotional well-being and family stability, as well as making a positive contribution to a more inclusive and equitable society